Construction of womanhood : reading Wide Sargasso Sea (1966), The God of Small Things (1997), A Golden Age (2007) and The Good Muslim (2011) - Shifa, Jannat Ara (BRAC University, 2015)
This thesis is submitted in partial fulfillment of the requirements for the degree of Masters of Arts in English, 2015.